Linking isoprene with plant thermotolerance, antioxidants and monoterpene emissions - Penuelas, J; Llusia, J; Asensio, D; MUNNÉ-BOSCH, S (Plant, Cell & Environment, 2005)
The purpose of the present study was to test the possible plant thermotolerance role of isoprene and to study its relationship with non-enzymatic antioxidants and terpene emissions. The gas exchange, chlorophyll fluorescence, extent of photo- and oxidative stress, leaf damage, mechanisms of photo- and antioxidant protection, and terpene emission were measured in leaves of Quercus ilex seedlings exposed to a ramp of temperatures of 5 °C steps from 25 to 50 °C growing with and without isoprene (10 µL L−1) fumigation. The results showed that isoprene actually conferred thermotolerance (shifted the decrease of net photosynthetic rates from 35 to 45 °C, increased Fv/Fm at 50 °C from 0.38 to 0.65, and decreased the leaf area damaged from 27 to 15%), that it precluded or delayed the enhancement of the antioxidant non-enzymatic defence conferred by α-tocopherol, ascorbic acid or β-carotene consumption in response to increasing temperatures, and that it decreased by approximately 70% the emissions of monoterpenes at the highest temperatures. This suggests that there are inducible mechanisms triggered by the initial stages of thermal damage that up-regulate these antioxidant compounds at high temperatures and that these mechanisms are somehow suppressed in the presence of exogenous isoprene, which seems to already exert an antioxidant-like behaviour.
Keywords: antioxidants; ascorbic acid; fumigation; Fv/Fm; high temperatures; isoprene; Monoterpenes; photosynthetic rates; thermotolerance; zeaxanthin; α-tocopherol; β-carotene